1993
DOI: 10.1111/j.1600-0897.1993.tb00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen Induced Production of Polyclonal IgG is Decreased in Women With Severe Endometriosis

Abstract: Since the number of circulating B cells was similar in each patient group studied, the reduced production of IgG2 in patients with stage 3 or 4 disease was not merely due to fewer antibody producing cells in those subjects, and we speculate that the observed decrease in polyclonal IgG2 production among these patients is due to a primary defect. In additional studies, we observed that polyclonal IgG2 production was normal among stage 3 or 4 patients treated with danazol (N = 11), but significantly reduced in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…The production of immunoglobulins by B lymphocytes is dependent, among other things, on the action of cytokines. Gebel et al [38] documented that in vitro IgG2 production after the stimulation of B lymphocytes was significantly reduced among women with stages III or IV of endometriosis in comparison to the healthy controls [38]. In this study, a similar tendency in values of total serum IgG concentration in stages III and IV of the endometriosis group was observed.…”
Section: Discussionsupporting
confidence: 78%
“…The production of immunoglobulins by B lymphocytes is dependent, among other things, on the action of cytokines. Gebel et al [38] documented that in vitro IgG2 production after the stimulation of B lymphocytes was significantly reduced among women with stages III or IV of endometriosis in comparison to the healthy controls [38]. In this study, a similar tendency in values of total serum IgG concentration in stages III and IV of the endometriosis group was observed.…”
Section: Discussionsupporting
confidence: 78%
“…The increase in serum concentration of soluble CD23, which is produced from activated B lymphocytes, in patients with endometriosis 65 also indicates enhanced activation of B lymphocytes. In contrast, IgG2 production by circulating B cells stimulated with polyclonal B‐cell activators was decreased in women with severe endometriosis, which may imply B‐cell dysfunction in advanced endometriosis 66 …”
Section: B Lymphocytesmentioning
confidence: 91%
“…They also described higher concentration of soluble CD23 in patients with stage I and II endometriosis, suggesting that mild endometriosis may be immunologically more active than severe endometriosis. Gebel et al (1993) findings also agree with this statement as they have reported reduced polyclonal IgG2 production in stage III and IV endometriosis.…”
Section: The Role Of B Lymphocytes and Immunoglobulins In The Pathogenesis Of Endometriosissupporting
confidence: 90%
“…Most studies demonstrated increased number and/or activation of B cells Gleicher et al, 1987;Scheerer et al, 2016), seven studies found no difference Gebel et al, 1993;Nava Loya et al, 1996; and two studies showed decreased number of B cells Gagne et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation